PENGARUH SARANA DAN PRASARANA PENDIDIKAN TERHADAP MOTIVASI BELAJAR SISWA DI SMP LABORATORIUM PERCONTOHAN UPI BANDUNG - Wani Wandikbo (Jurnal Tata Kelola Pendidikan, 2021)
This study aims to determine the effect of educational facilities and infrastructure on student motivation in SMP Laboratorium Percontohan UPI Bandung. The method used in this research is descriptive method with a quantitative approach. The data collection technique used a questionnaire to the respondents which was distributed to 46 junior high school students, the Pilot Laboratory of the University of Bandung, Bandung as the research sample. The results of the calculation of the correlation analysis using the Pearson product moment, obtained the correlation coefficient between variables X and Y is 0.750 which is in the coefficient interval from 0.600 to 0.799 so that it is at the level of a strong relationship. The results of the significance test between the X variable (Educational Facilities and Infrastructure) and the Y variable (Student Learning Motivation) SMP Laboratorium Percontohan UPI Bandung obtained t count ≥ t table, namely 2,924 ≥ 2,015 so it can be said to be significant. Furthermore, the coefficient of determination test results showed that educational facilities and infrastructure contributed 56.25% to students' learning motivation while the remaining 43.75% (100% -56.25) was influenced by other factors. The conclusion of this study states that there is a relationship strong and significant between the influence of educational facilities and infrastructure on student motivation in SMP Laboratorium Percontohan UPI Bandung.